2021
DOI: 10.2174/1566524020666200521080953
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Induces Apoptosis and Attenuates Proliferation of MCF-7 Cells in Combination with Radiation and Hyperthermia

Abstract: Aim: In the current in vitro study, we tried to examine the possible role of resveratrol as a sensitizer in combination with radiotherapy or hyperthermia. Background: Breast cancer is the most common malignancy for women and one of the most common worldwide. It has been suggested that using non-invasive radiotherapy alone cannot eliminate cancer cells. Hyperthermia which is an adjuvant modality induces cancer cell death mainly through apoptosis and necrosis. However, cancer cells can also develop resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Resveratrol is one of the natural agents that have shown low toxicity to normal tissues and also have several properties that make it an anticancer agent. In addition to the preventive effects of resveratrol, several studies have confirmed that resveratrol can kill cancer cells via induction of various mechanisms (Amini et al, 2020). Resveratrol has been shown to induce the release of IL‐2, IL‐4, and IFN‐γ by immune cells, which potentiate the proliferation of CD4+ and CD8+ T lymphocytes, and also NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol is one of the natural agents that have shown low toxicity to normal tissues and also have several properties that make it an anticancer agent. In addition to the preventive effects of resveratrol, several studies have confirmed that resveratrol can kill cancer cells via induction of various mechanisms (Amini et al, 2020). Resveratrol has been shown to induce the release of IL‐2, IL‐4, and IFN‐γ by immune cells, which potentiate the proliferation of CD4+ and CD8+ T lymphocytes, and also NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that among the studied stilbene derivatives, resveratrol has the greatest ability to strengthen the effect of IR in the MCF-7 cell line. Recently published studies by Amini et al also showed that resveratrol potentiated the effects of radiation on MCF-7 cells [33].…”
Section: Discussionmentioning
confidence: 96%
“…There are some reasons for selecting plant derived‐natural products that can be their low side effects, high safety profile, multitargeting capacity, and lack of drug resistance in tumor cells (Ahn, Sethi, & Aggarwal, 2008; F. Halim et al, 2019; Kashyap et al, 2021; Li, Shanmugam et al, 2015). Furthermore, phytochemicals are affordable and developing countries can utilize them in the treatment of cancer patients (Amini et al, 2021; Ashrafizadeh, Rafiei et al, 2021; Ashrafizadeh, Zarrabi, Orouei, Saberifar et al, 2021; Deldar Abad Paskeh, Asadi et al, 2021; Hashemi et al, 2021; Hussain et al, 2021; Samec et al, 2021). This section focuses on recent studies using antitumor agents in modulating NF‐κB/EMT axis.…”
Section: Selected Antitumor Compounds Targeting Nf‐κb/emt Axismentioning
confidence: 99%